In Vitro Inhibition of Blood Coagulation by Tripeptide Aldehydes - A Retrospective Screening Study Focused on the Stable D-MePhe-Pro-Arg-H · H2SO4 - Bágdy, Daniel; Barabás, Èva; Bajusz, Sándor; Széll, Erzsébet (Thrombosis and Haemostasis, 1992)
A series of peptide aldehydes synthetized in our institute during the last 15 years were screened to detect their inhibitory effect on blood coagulation. Simple conventional clotting assays, platelet function tests and fibrinolytic methods were used to evaluate the inhibitory potency of the compounds in complex clotting systems as well as their supposed antifibrinolytic effect in vitro. Special attention was paid to the possible interactions with blood cells and plasma proteins, and to the functional stability of the inhibitors in several tissue homogenates. D-Phe-Pro-Arg-H (GYKI-14166, RGH-2958), Boc-D-Phe-Pro-Arg-H (GYKI-14451) and D-MePhe-Pro-Arg-H (GYKI-14766) were found to be the most potent inhibitors. The peptide aldehydes via formation of reversible complexes with thrombin impede the enzyme to react with the coagulation factors, platelet membrane and vessel wall. The compounds inhibit platelet aggregation induced by thrombin specifically without changing the sensitivity of platelets to other inducers. D-Phe-Pro-Arg-H and D-MePhe-Pro-Arg-H showed no antifibrinolytic effect. D-MePhe-Pro-Arg-H and Boc-D-Phe-Pro-Arg-H proved to be stable in dry state for years and in solution at room temperature for several days. The anticoagulant activity of the compounds was declared in NIH antithrombin units.